THE ROLE OF TQM PRACTICES IN FOSTERING INNOVATION IN MALAYSIAN ARMY TRAINING INSTITUTION - Rahmat , Mat Sahari; Mohamed , Hasan Al-Banna; Liaw , Jessica Ong Hai; Basiron , Mohd Kenali; Shari, Muhmad Zafferi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
This paper addresses the Total Quality Management (TQM) practices in Malaysian Army training institutes, which impedes the delivery of high-quality training necessary for national military readiness amid rapid technological advancements. This study aims to examine the impact of top management commitment, employee empowerment, and teamwork as a key component of TQM practices on innovation within these institutions. The study employed quantitative methods, specifically correlation and regression analysis, utilizing data from 387 military personnel. The findings indicated significant positive correlations between innovation and top management (r = 0.618), employee empowerment (r = 0.665), employee involvement (r = 0.597) and teamwork (r = 0.515). The regression analysis indicates that employee empowerment exerts the most significant influence on creativity (beta = 0.398), succeeded by top management commitment (beta = 0.318) and teamwork (beta = 0.117). All of these findings are statistically significant. The findings underscore the significance of leader involvement, employee empowerment, and a collaborative culture in fostering creativity within military training. The report recommends tailored training and leadership development for a predominantly young, mid-career workforce, promoting collaboration, adapting programs to suit educational and regional contexts, and implementing continuous evaluation through statistical methods to sustain innovative initiatives. This study examines the influence of Total Quality Management (TQM) practices on promoting innovation within defense training environments, thereby enabling strategic improvements essential for contemporary military effectiveness.